Exhumation of the western Qinling mountain range and the building of the northeastern margin of the Tibetan Plateau. (15th June 2019) - Zattin, Massimiliano; Wang, Xiuxi
Graphical abstract: Highlights: The region north of West Qinling Fault exhumed at low rates since the Cretaceous. The southern block was affected by enhanced exhumation in the Eocene. The Western Qiniling Fault was active as a thrust in the Cretaceous. Regional transtensional tectonics occurred during the Eocene. A Cretaceous relief was disrupted by the Eocene transtension. Abstract: This study presents new apatite fission-track data collected from intrusive and sedimentary rocks of the western Qinling mountain range. Results show a large range of data, with ages spanning from Upper Jurassic to Oligocene. No particular age-elevation relationships have been detected. Thermal modelling shows clearly that the region was affected by a nearly steady-state slow cooling starting from the Jurassic. This is particularly true for samples collected north of the West Qinling Fault whereas samples collected to the south show a re-heating event, followed by enhanced exhumation. As a whole, these data testify that the studied part of the western Qinling region was relatively stable for a long period and relatively insensitive to the tectonics related to the growth of the Tibetan Plateau. The present-day relief is mainly the result of transtensional tectonics that occurred in the Eocene.